Pitch and Loudness from Tinnitus in Individuals with Noise-induced Hearing Loss - Flores,Leticia Sousa (2016)
Abstract Introduction Tinnitus is one of the symptoms that affects individuals suffering from noise induced hearing loss. This condition can be disabling, leading the affected individual to turn away from work. Objective This literature review aims to analyze the possible association between gender and tinnitus pitch and loudness, the degree of hearing loss and the frequencies affected in subjects with noise-induced hearing loss. Methods This contemporary cohort study was conducted through a cross-sectional analysis. The study sample consisted of adults with unilateral or bilateral tinnitus, who had been diagnosed with noise-induced hearing loss. The patients under analysis underwent an otorhinolaryngological evaluation, pure tone audiometry, and acuphenometry. Results The study included 33 subjects with noise-induced hearing loss diagnoses, of which 22 (66.7%) weremen. Authors observed no statistical difference between gender and loudness/pitch tinnitus and loudness/pitch in subjects with bilateral tinnitus. Authors found an inverse relation between tinnitus loudness with intensity greater hearing threshold and the average of the thresholds and the grade of hearing loss. The tinnitus pitch showed no association with higher frequency of hearing threshold. Conclusion Data analysis shows that, among the individuals evaluated, the greater the hearing loss, the lower the loudness of tinnitus. We did not observe an association between hearing loss and tinnitus pitch.